Bioelectrical Impedance Vectors Analysis of Sarcopenic Older Adults Submitted to a Resistance Training Program - Quizzini, Giovanni Henrique [UNESP]; de Souza Pereira, Caroline Galan [UNESP]; dos Santos, Vanessa Ribeiro [UNESP]; Batista, Vitor Cabrera [UNESP]; de Alencar Silva, Bruna Spolador [UNESP]; Lira, Fábio Santos [UNESP]; Ribeiro, Alex Silva; Gobbo, Luís Alberto [UNESP] (Wiley, 2024)
The objective of the present study is to analyze the changes in bioimpedance vector analysis (BIVA) and phase angle (PhA) in sarcopenic older people submitted to a 12-week resistance training (RT) program according to classic and specific analyses. To this end, 20 sarcopenic older adults of both sexes, invited through media, underwent bioimpedance analysis before and after the RT carried out three times a week, for 12 weeks. The mean impedance vectors of the groups established for the confidence ellipses (95% of the confidence ellipse) are compared using Hotelling's T2 test. The distance D from Mahalanobis is also calculated. Classic and Specific BIVA are presented. The resistance values for the classical analyses (R/H) decreased across all groups (whole group, women and men, p < 0.05), with approximate decreases ranging from 9.4% to 10%, while the classic reactance (Xc/H) decreased (p < 0.05) only for the whole group (5.9%) and men (7.7%). For the specific BIVA, trends are verified for the whole sample, with a decrease in resistance (R.sp) and an increase in reactance (Xc.sp). In conclusion, the RT program in sarcopenic individuals promoted a reduction in resistance values in classical analyses, indicating a possible increase in hydration status and, consequently, musculoskeletal mass.